(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
This article aims to discern about the didactic experience in teaching visual syntax content delimited in compositional practice. The research is qualitative, whose data and information collection strategies used were bibliographic and systematic research in a scientific work bank. Next, some examples of historical landmarks that support the discussion about the programmatic content of academic activity are described. At the end, a discernment about this content in the academic formation of this future professional is presented, verifying tensions in the teaching-learning of the syntactic foundations of visual language in Graphic Design.